Field Service System / Khoo Chai Ee - Khoo , Chai Ee (2004)
Field Service System is a web-based system that streamline and automates the field service function in order to create new revenue opportunities retaining the customer and making the field service organization staying ahead of the competition. Microsoft Active Server Page.NET (ASP.NET) is chosen a the application language to develop the system. Microsoft SQL Server 2000 is selected as the data store with ADO.NET as data access technology. Internet Information Server 5.o acts as the web server while Internet Explorer 6.0 is the web browser that can support the system. The 3-tier architecture is used in developing the system. The Field Service System consists of 6 major modules: Login module, Service Call Managemen for the customer, User Management for system administrator, Sales Management for sales department, Dispatch Management for the technical manager and Work Order Management for the technician. For the customers, they can request service and check ther order staus. The system administrator can manage and monitor all the system's users. For the customers, they can request service and check the order status. The system administrator can manage and monitor all the system's users. For the sales & marketing department, they cant track and control parts/ components and customers's data more systematically. The technical manager can increase technician's productivity by assigning appropriately skilled technician, read closed work order report and generate reports. Besides that, the technicians can remain in contact with their home base. They can access the customer's service agreement information, installed equipment, work order history, parts availability and etc online.